2008
DOI: 10.1002/mrm.21443
|View full text |Cite
|
Sign up to set email alerts
|

B compensation in 3T cardiac imaging using short 2DRF pulses

Abstract: The purpose of this study was to determine if tailored 2DRF pulses could be used to compensate for in-plane variations of the transmitted RF field at 3T. Excitation pulse profiles were designed to approximate the reciprocal of the measured RF transmit variation where the variation over the left ventricle was approximated as unidirectional. A simple 2DRF pulse design utilizing three subpulses was used, such that profiles could be quickly and easily adapted to different regions of interest. Results are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…Both spatial excitation (flip angle) variations and an imperfect slice profile likely played a role in the findings of a net flip angle for the blood region of 8.5 ± 2.2 degrees, instead of the 14° that was designated in the radial perfusion sequence. This nearly 40% reduction in flip angle is similar to that found previously in the heart at 3T [22]. A 23-48% variation in flip angle across the heart has also been reported at 3T [23].…”
Section: Discussionsupporting
confidence: 87%
“…Both spatial excitation (flip angle) variations and an imperfect slice profile likely played a role in the findings of a net flip angle for the blood region of 8.5 ± 2.2 degrees, instead of the 14° that was designated in the radial perfusion sequence. This nearly 40% reduction in flip angle is similar to that found previously in the heart at 3T [22]. A 23-48% variation in flip angle across the heart has also been reported at 3T [23].…”
Section: Discussionsupporting
confidence: 87%
“…A critical component of the SDAM method is the saturation or reset pulse because of its sensitivity to B 0 and B 1 + inhomogeneities. In this study, an 8‐ms BIR‐4 pulse was applied and has successfully been used at 3 T (12–14). Recently, it has been shown that a tailored hard‐pulse train results in better saturation and less RF power deposition compared to an 8‐ms BIR‐4 saturation pulse (22).…”
Section: Discussionmentioning
confidence: 99%
“…Applying SDAM, Sung and Nayak (13) reported a flip angle variation ranging from 31 to 66% over the entire left ventricle volume. As the variation was predominantly unidirectional in short‐axis (SA) slices, they proposed to use 3‐ms‐long two‐dimensional RF pulses to reduce the average flip angle variation in SA slices over the left ventricle by 41% (14). Sung and Nayak (13) reported a flip‐angle distribution from 34° to 63° across the left ventricle, for a nominal flip angle of 60°.…”
mentioning
confidence: 99%
“…As a result, the reconstructed images will have shading artifacts, variable contrast and lower SNR. These artifacts can be corrected using RF pulses that do not depend on field homogeneity, such as adiabatic pulses [32][33][34], or by directly compensating for the nonuniformity when designing the pulse [35]. Angiography results demonstrating the improvement in image quality using adiabatic pulses are shown in Figure 6.…”
Section: System Limitations and Imperfectionsmentioning
confidence: 95%